Parental Percetion of the Teaching of Sex Education to Adolescent in Secondary School in Cross River State, Nigeria - Akpama, Elizabeth G (Himalayan Journal of Sociology and Anthropology, 2014)
This study was an ex-post facto research, design to determine parental perception of the teaching of introducing sex education to adolescents in secondary schools in Cross River State, as the area of study. Two null hypotheses were formulated on the basis of the identified major independent variables of nature of parental perception and parental literacy status. A 15-item questionnaire was developed, validated and tested for reliability. It was then administered to 400 respondents (parents–200 male, 200 female) from 20 churches in the entire state (7 churches from central, 7 from south and 6 from north senatorial districts). The sample was selected by stratified cluster and simple random procedure. Data was analysed using the independent t-test. Results revealed that parental perception of the teaching of sex education to adolescents in secondary schools is significantly negative; no significant difference exists between literate and illiterate parents in their perception of the teaching of sex education to adolescents in secondary schools. It was concluded that parental perception of the teaching of sex education to adolescents in secondary schools is generally negative in Cross River State. Some recommendations were enhanced as the way forward. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10714 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 134-145